IMPLEMENTATION OF E-SAPAWARGA SYSTEM IN EFFORTS TO IMPROVE GOVERNMENT SERVICES IN SURABAYA (Universitas 17 Agustus 1945 Surabaya, 2021)
The purpose of this study is to describe the use of E-sapawarga in an effort to improve government services in Surabaya. The E-Sapawarga program is run through an application called